The Violet’s Failures to Save Finch From Suicide As Seen in Niven’s All The Bright Places - Helmita, Helmita; Telaumbanua, Pancasona (Fakultas Sastra Universitas Ekasakti, 2025)
This research focuses on the main character, Violet, as well as the factors that influence her personality. To gain insight into Violet's soul as depicted in the novel All The Bright Places, this research aims to learn from Violet's failures in saving Finch, so that they do not happen again in the future.Researchers use observational methods in data collection based on Kothari. (2004). The data collection technique used for this research is reading and noting the instances of Violet's failures in saving Finch from suicide in the novel All The Bright Places and identifying Violet's personality traits found within the novel.The theoretical framework used in this research is Carl Jung's personality theory (2008), which specifically examines archetypes such as Anima, Animus, and Self. The researcher employs descriptive and qualitative methods in this study. According to research findings in the novel All The Bright Places, Violet's personality is greatly influenced by the Anima, Animus, and Self within her, which results in Violet's lack of sensitivity towards Finch, who desperately needs attention and support to avoid struggling with past trauma, as explained in the novel All The Bright Places.